The need for a more inclusive science of elephant conservation. Issue 5 (21st April 2020) - Cassidy, Lin; Salerno, Jonathan
Abstract: Largely absent from the current scientific dialog is recognition of which voices should contribute to decisions on the future of Africa's elephants, particularly those living in the Kavango‐Zambezi Transfrontier Conservation Area. We argue that elephant conservation policy must take into account the voices of the people bearing the cost of living with wildlife, as well as the nations with the responsibility of hosting elephant populations. Southern African elephant conservation is a 'wicked problem', which is best addressed through small wins approaches. Specifically, research on changes in local political and governance dynamics resulting from community conservation programs is needed, to identify new modalities for community level engagement. Additionally, research into policy implications, as well as seasonal resource needs of humans and wildlife, from zoning and corridor development to facilitate landscape level movement is needed. A modular approach to research for ensuring functional social–ecological landscapes within the KAZA context could help sustain both wildlife and communities in the region.